Chilean blue whales off Isla Grande de Chiloe, 2004-2010: distribution, site-fidelity and behaviour - Vernazzani, Barbara Galletti; Carlson, Carole A.; Cabrera, Elsa; Brownell Jr., Robert L. (J. Cetacean Res. Manage., 2023)
A collaborative research program (the Alfaguara Project) has collected information on Chilean blue whales (Balaenoptera musculus) off Isla Grande de Chiloe, in southern Chile, through eight aerial and 85 marine surveys. A total of 363 individual blue whales was photo-identified from 2004 to 2010. Approximately 20% of all catalogued individuals were resighted within the same season and 31% were resighted between years. Recaptures of photo-identified individuals from other areas to the north and south of the main study area support the hypothesis that the feeding ground off southern Chile is extensive and dynamic. The high overall annual return and sighting rates highlight the waters off northwestern Isla de Chiloe and northern Los Lagos as the most important aggregation areas currently known for this species in Chile and one of the largest in the Southern Hemisphere. Observations on feeding and social behaviour also were recorded. These results provide important information on the conservation status of Chilean blue whales and highlight the necessity that long-term photographic identification research and line-transect surveys to monitor health conditions and population trends be continued off northwestern Isla de Chiloe. The high frequency of large vessels in the mouth of the Chacao Channel (along the north side of Isla de Chiloe) and the high number of blue whales in the area raises the possibility of vessel collisions. Therefore, it is necessary to develop and implement a conservation plan for these whales to address this and other potential threats.